1984
DOI: 10.1007/bf02540810
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of seed oils of the meliaceae, including one genus rich incis‐vaccenic acid

Abstract: The seed tipids of three species of Entandrapbragma (Meliaceae) contain the largest proportion (31-50%) of ds-vaccenic acid ever found in nature. The acid is not indicative of the family as a whole and is found as a major fatty acid in the seed of only one additional species, besides Entandrapbragma, out of the 30 analyzed from this family. With the total oil comprising between 45 and 62% of Entandrapbragma seed, these species should be considered as a source of undecadioic acid for the production of nylon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The fatty acids found were palmitic, stearic, oleic, linoleic and punicic for T. anguina and palmitic, stearic, arachidic, oleic, linoleic and linoleinic for S. mahogani seed oils. These results partially agree with the findings of other [8,10,29]. The differences in our results from them could be explained by variations in soil and climatic conditions.…”
Section: Fatty Acid Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…The fatty acids found were palmitic, stearic, oleic, linoleic and punicic for T. anguina and palmitic, stearic, arachidic, oleic, linoleic and linoleinic for S. mahogani seed oils. These results partially agree with the findings of other [8,10,29]. The differences in our results from them could be explained by variations in soil and climatic conditions.…”
Section: Fatty Acid Compositionsupporting
confidence: 92%
“…Total protein (N×6.25) of S. mahagoni seeds was 13.0% of which 7.5% was water soluble. The protein content in S. mahagoni seeds agrees with the value 13.5% reported by Kleiman and Payne-Wahl [8] for the same seed oil. Findings in the present results revealed that the T. anguina seed is qualified as protein-rich to satisfy the protein needs of the consuming population.…”
Section: Nutritional Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…In analyses it is always added to the amount of oleic acid (Kleiman and Payne-Wahl 1984). Three dierent intraplastidial biochemical pathways have been proposed for its biosynthesis: (i) elongation of palmitoleic acid (16:1 D9) mediated by FASII (con®rmed by Shibahara et al 1989), (ii) isomerization of oleic acid to asclepic acid (con®rmed by Shibahara et al 1990), and (iii) desaturation of stearoyl-ACP mediated by a speci®c D11-desaturase (proposed by Kleiman and Payne-Wahl 1984). The following results from our mutants point to the ®rst proposal as the biosynthetic pathway in sunower seeds.…”
Section: Discussionmentioning
confidence: 99%
“…These two enzyme preparations were tested under different supercritical conditions in order to select the most suitable enzyme preparation as well as the optimal SFE parameters for the simultaneous extraction and methanolysis of oil from milkweed (Asclepias) seeds. cis-Vaccenate was chosen as the target analyte as it has potential industrial uses, including for engineering plastics (21,22) and as an antifungal agent (23). Furthermore, vaccenic acid is converted in mammals to CLA, which suppresses cancer and atherosclerosis, and enhances the immune system and the development of lean muscle mass (24).…”
mentioning
confidence: 99%